Decision factors for remote work adoption: Advantages, disadvantages, driving forces and challenges - Ferreira, R (2021)
Facing one of the most challenging pandemics for organizational modus operandi (COVID-19), organizations are struggling for operational and strategic support. The adoption of remote work (RW) is increasing. For economic reasons, competitive advantage, or even as a pandemic response (business continuity plan), RW is a domain worth further investigation. However, the literature lacks insight regarding RW adoption. A design science research methodology was adopted, including a systematic literature review to elicit RW advantages, disadvantages, challenges and driving forces, as well as their relation. To evaluate and demonstrate findings, 129 qualitative interviews were performed with RW professionals. In the end, 57 decision factors were elicited, and 16 relations were validated. The authors concluded that cost-reduction and flexibility to promote work–life balance is the most positive outputs, while communication and technical problems, as well as management issues, are what most concerns professionals. Moreover, positive relations are more recognized among professionals over negative ones.